Efek pemberian ekstrak etanol bawang putih (Allium sativum) sebagai hepatoprotektor pada tikus putih jantan galur wistar (Rattus norvegicus) yang diinduksi parasetamol dosis hepatotoksik - Made Subhawa Harsa (DiscoverSys Inc., 2020)
Garlic (Allium sativum) is a plant that known to have various properties that can be used in treatment as a hepatoprotective agent. This study aim was to determine the effect of garlic ethanol extract (Allium sativum) in Wistar strain white male rats (Rattus norvegicus) which was induced by paracetamol in hepatotoxic dose. This research is an experimental study with randomized the post-test only control group design with sample consisted of twenty-four Wistar strain white male rats (Rattus norvegicus). The sample were divided into four groups: control groups, group P1 (given garlic ethanol extract 10 mg/kg), group P2 (ethanol extract of garlic was given 20 mg/kg) and group P3 (given the ethanol extract garlic 30 mg/kg). This study for seventeen days. The entire samples were terminated in order to draw blood to examine SGPT and SGOT. The data of SGPT and SGOT examined by One Way ANOVA. Result showed that there was significant difference in SGPT and SGOT values between groups after given ethanol extract of garlic (Allium sativum) (Î± <0.05). From the analysis we can concluded that garlic ethanol extract (Allium sativum) can be used as a hepatoprotective agent in Wistar strain white male rats (Rattus norvegicus) Â induced by paracetamol in hepatotoxic dose.